Malapropisms in the Spanish Translations of Joseph Andrews - Alpuente Civera, Miguel (Meta, 2012)
Malapropisms have received little specific attention in studies concerning the translation of humorous phenomena, as researchers have usually addressed the broader category of wordplay. Malapropisms, however, while a subtype of wordplay, also represent a phenomenon in their own right, and their longstanding use as a humorous device in literature, as well as the particular translation problems they pose, largely justify a separate analysis. Additionally, more often than not, the translation of malapropisms has been addressed from a prescriptive point of view. Therefore, in addressing the translation of malapropisms in the Spanish versions of Joseph Andrews, this paper has a double aim. Firstly, it seeks to highlight the need for a comprehensive framework of analysis capable of singling out the particular features of malapropisms within a given text, paying attention most notably to their function in the text as a whole, their typological range, and the translation techniques employed to deal with them, as well as some extratextual factors that may help explain certain decisions taken by translators and their degree of acceptance within the target literary system. Secondly, it draws attention to descriptive analysis, showing how, by improving knowledge of the phenomena involved, it can prove useful for further translations.